On ga-compact spaces - Saraf, Ratnesh K.; Caldas, Miguel (Pro Mathematica, 2000)
The purpose of this paper is to introduce and discuss the concept of g?-compactness for topological spaces. An example is considered to show that it is strictly stronger than that of compactness.